The Role of Laboratory Activities on Laundry Industry Waste Pollution to Improve Problem Solving skills: Teacher's Perception - Kusnia, Dina Kiftatul; Fadiawati, Noor; Setyarini, M. (FKIP Universitas Lampung, 2022)
This study aims to describe the teacher's perception of problem-solving-based laboratory activities to improve the problem-solving skills of junior high school. This study involved 30 science teachers in Lampung. Collecting data in this study using a questionnaire, then analyzed using descriptive analysis. The survey results show that 65% of science teachers have not carried out problem-solving-based laboratory activities in their learning activities. This is due to several factors including teachers not being able to manage time in learning activities and limited tools and materials in school laboratories. Whereas on environmental pollution material for class VII of Junior High School, students can be invited to carry out laboratory activities based on solving real problems such as water pollution by laundry industrial waste. Based on the survey results, it can be said that the laboratory activity program is needed by teachers and students to improve students' problem solving skills.Keywords: laboratory activities, problem-based learning, problem solving skills.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp327-334